Action potential bursts in central snail neurons elicited by paeonol: roles of ionic currents - Chen Yi-hung; Lin Pei-lin; Hsu Hui-yu; Wu Ya-ting; Yang Han-yin; Lu Dah-yuu; Huang Shiang-suo; Hsieh Ching-liang; Lin Jaung-geng (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the effects of 2′-hydroxy-4′-methoxyacetophenone (paeonol) on the electrophysiological behavior of a central neuron (right parietal 4; RP4) of the giant African snail (Achatina fulica Ferussac). Methods: Intracellular recordings and the two-electrode voltage clamp method were used to study the effects of paeonol on the RP4 neuron. Results: The RP4 neuron generated spontaneous action potentials. Bath application of paeonol at a concentration of ≥500 μmol/L reversibly elicited action potential bursts in a concentration-dependent manner. Immersing the neurons in Co2+-substituted Ca2+-free solution did not block paeonol-elicited bursting. Pretreatment with the protein kinase A (PKA) inhibitor KT-5720 or the protein kinase C (PKC) inhibitor Ro 31-8220 did not affect the action potential bursts. Voltage-clamp studies revealed that paeonol at a concentration of 500 μmol/L had no remarkable effects on the total inward currents, whereas paeonol decreased the delayed rectifying K+ current (IKD) and the fast-inactivating K+ current (IA). Application of 4-aminopyridine (4-AP 5 mmol/L), an inhibitor of IA, or charybdotoxin 250 nmol/L, an inhibitor of the Ca2+-activated K+ current (IK(Ca)), failed to elicit action potential bursts, whereas tetraethylammonium chloride (TEA 50 mmol/L), an IKD blocker, successfully elicited action potential bursts. At a lower concentration of 5 mmol/L, TEA facilitated the induction of action potential bursts elicited by paeonol. Conclusion: Paeonol elicited a bursting firing pattern of action potentials in the RP4 neuron and this activity relates closely to the inhibitory effects of paeonol on the IKD.